Reasoning about river basins: WaWO+ revisited. (March 2017) - Oliva-Felipe, L.; Gómez-Sebastià, I.; Verdaguer, M.; Sànchez-Marrè, M.; Poch, M.; Cortés, U.
Abstract: This paper characterizes part of an interdisciplinary research effort on Artificial Intelligence (AI) techniques and tools applied to Environmental Decision-Support Systems (EDSS). WaWO + the ontology we present here, provides a set of concepts that are queried, advertised and used to support reasoning about and the management of urban water resources in complex scenarios as a River Basin. The goal of this research is to increase efficiency in Data and Knowledge interoperability and data integration among heterogeneous environmental data sources ( e.g., software agents) using an explicit, machine understandable ontology to facilitate urban water resources management within a River Basin. Highlights: Ontology to support reasoning in Urban Wastewater Systems. Knowledge representation of river basin domain and legislation. Extends a previous ontology focused on WWTP internals, including other stakeholders: households and industries.